ChemInform Abstract: A Fluorination/Aryl Migration/Cyclization Cascade for the Metal‐Free Synthesis of Fluoro‐Benzoxazepines. Issue 30 (July 2016) - Ulmer, Anna; Brunner, Christoph; Arnold, Andreas M.; Poethig, Alexander; Gulder, Tanja
Abstract: The efficient, regioselective method is based on an operationally simple fluorination of readily available, structurally diverse styrene derivatives with a hypervalent iodine(III) fluoro reagent.